2018
DOI: 10.1021/acs.jpcc.8b04751
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Decomposition of Formic Acid on Cobalt(0001)

Abstract: Formic acid can undergo dehydration or dehydrogenation with variable selectivity over a range of metal catalysts. The selectivity among these reactions depends on the reaction mechanism and reaction conditions pertinent on each surface. This work provides mechanistic insight on the decomposition of formic acid on cobalt at high and low temperature regimes. The adsorption and decomposition of formic acid on a Co(0001) single crystal was studied in ultra-high vacuum by X-ray photoelectron spectroscopy (XPS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…FA decomposition on various late transition-metal surfaces such as Pd, 8−12 Rh, 13−15 Ru, 16,17 Pt, 18−20 Cu, 21−23 Co, 24 Ag, 25 as well as Pd−Ag 26 and Pd−Au 27 bimetallic systems, has been extensively studied under ultrahigh vacuum (UHV) conditions. These studies showed that many high-coordination transition-metal single-crystal surfaces were capable of carrying out FA dehydrogenation effectively.…”
Section: Introductionmentioning
confidence: 99%
“…FA decomposition on various late transition-metal surfaces such as Pd, 8−12 Rh, 13−15 Ru, 16,17 Pt, 18−20 Cu, 21−23 Co, 24 Ag, 25 as well as Pd−Ag 26 and Pd−Au 27 bimetallic systems, has been extensively studied under ultrahigh vacuum (UHV) conditions. These studies showed that many high-coordination transition-metal single-crystal surfaces were capable of carrying out FA dehydrogenation effectively.…”
Section: Introductionmentioning
confidence: 99%
“…FA decomposition on several group-VIII transition-metal surfaces such as Pd, 12−16 Rh, 17−19 Ru, 20,21 Pt, 22−24 Cu, 25−27 Co, 28 Ag, 29 and their bimetallic combinations 30 has been extensively studied under ultrahigh vacuum (UHV) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…102 In accord with the most favourable binding modes suggested by experimental studies and DFT/metadynamics calculations, initial forms of interaction of acetic acid, ethanamine, and ethanethiol molecules were bridging bidentate, bridging monodentate, and three-fold monodentate, respectively. 44,[95][96][97][98] No changes in the interaction modes were observed upon the structural optimisation. Density of the passivating coating was determined as the number of Co atoms interacting with adsorbed molecules over the total number of surface Co atoms, where full coverage is reached once every surface Co atom interacts with one ligand molecule through a single bond.…”
Section: Resultsmentioning
confidence: 98%